1997
DOI: 10.1017/s002221510013885x
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculoma of the cheek: a case report

Abstract: Tuberculoma of the cheek in the absence of tuberculosis elsewhere in the body is rarely seen and hence rarely thought of as a differential diagnosis when such a patient presents.In the following case, the patient was provisionally diagnosed as carcinoma of the cheek because of the exophytic nature of the growth and its presentation. However, histopathology of a biopsy revealed tuberculoma and the response to antituberculous therapy was rapid and curative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The typical oral lesions consist of a stellate ulcer, most commonly on the dorsum of the tongue site [5,6] other sites being gingiva, floor of mouth, palate, lips and buccal mucosa [7].…”
Section: Introductionmentioning
confidence: 99%
“…The typical oral lesions consist of a stellate ulcer, most commonly on the dorsum of the tongue site [5,6] other sites being gingiva, floor of mouth, palate, lips and buccal mucosa [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies reporting extra-oral involvement of the cheek in the past have involved fistula, 7 sinus 8 or ulceration of the cheek. 9 But this type of ulcerative and fungating lesion has never been reported. In our case there were multiple ulcers over the right cheek.…”
Section: Discussionmentioning
confidence: 99%
“…11 The tongue and gingiva are the most common sites of infection in patients with oral tuberculosis, followed by that of tooth sockets, soft palate, floor of mouth, lips, and buccal mucosa. 12 However, the occurrence of secondary lesions in the gingiva is rare; none of the cases reported by Mignogna et al 8 demonstrated gingival involvement. Orofacial lesions may appear as ulcers, 13 nodules, 7 fissures, tuberculomas, or granulomas 5 and are usually secondary to pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%